Kommunalreformen og kommunernes interne organisering og styring - Ibsen, Marius (Politik, 2016)
When local government in Denmark was reformed almost 10 years ago, the political and administrative organization was left unchanged. By law Danish municipalities must have a committee form of government, but each municipality is free to organize its administration as it sees fit. This had led to a great deal of diversity in the way the municipal administration is organized but also to a wave of locally directed reform. One of the themes of these reforms has been the organization of top management. Should each department be run more or less on its own, subject to coordination, or should there be a top management team collectively responsible for the whole enterprise. The article describes the variation in administrative organization and makes an attempt to analyze the effects of the various forms of top management organization with respect to economic results. The conclusion is that having a top management team leads to a bigger surplus, confirming an often-stated assumption. It is shown that municipalities that were reformed in 2007 are slightly more likely to have a top management team than the non-reformed municipalities. So it seems that the reform contributed to organizational change, although that was not the official intention.